Potensi Dan Prospek Pengembangan Tanaman Kakao (Theobroma cacao L.) Di Desa Antutan Kecamatan Tanjung Palas Kabupaten Bulungan: (Potential and prospects for the development of cocoa plants (Theobroma cacao L.) in Antutan Village, Tanjung Palas District, Bulungan Regency) - Rita Mariati; Syarifah Aida (Universitas Widya Gama Mahakam, 2023)
ABSTRACT Cocoa is a food commodity with high economic value that contributes to improving the welfare of farmers. This research was conducted to determine the cocoa plant development strategy by identifying internal and external factors of the cocoa plant in Antutan Village. This research was conducted in Antutan Village, Tanjung Palas District, Bulungan Regency from November 2022 to January 2023. Sampling used purposive sampling and stratified random sampling with a total sample of 28 cocoa farmers. Data analysis using the SWOT analysis method as well as analysis of the internal and external environment (IFAS and EFAS). Based on the SWOT analysis, the matrix calculation results are in quadrant I, namely the SO strategy or supporting an aggressive strategy. Where farmers can explore various potentials in business, take advantage of the availability of capital they have, improve post-harvest treatment for the better and utilize the ability of the workforce. Keywords: Cocoa, Potency, Strategy, Development, SWOT.